2014
DOI: 10.1179/1743284714y.0000000585
|View full text |Cite
|
Sign up to set email alerts
|

SCC behaviours of austenitic stainless steel Z3CN20-09M in high temperature water

Abstract: Stress corrosion cracking (SCC) behaviours of Z3CN20-09M stainless steel in high temperature water containing Cl− were studied. The results indicated that SCC sensitivity was inconsistent with test temperature. The minimum and maximum of SCC sensitivity occurred at 320 and 290°C respectively, and SCC sensitivity at 250°C fell between them. SCC crack initiated preferentially at bottom of corrosion pit or along phase boundary between austenite and ferrite, and its propagation depended on relative orientation to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…However, this does not seem to be the case for the material used for this study which cracks preferentially at the ferriteaustenite interface, representing ~50% of the cracks in both samples (for SSRT-T1 only propagation type has be considered since most of the cracks are initially transgranular but they become intergranular or follow a δ-γ interface after some penetration). Based on results from Y. H. Lu et al [20], this can be related to the sample orientation (S-L) used for this work that imply ferrite austenite interfaces are perpendicular to stress direction, i.e., δ -γ interfaces are parallel to crack propagation. This stimulates higher strain localisation at the interface (therefore, more cracks) in addition to the differences accommodating stresses between ferrite and austenite.…”
Section: Local Strainmentioning
confidence: 99%
“…However, this does not seem to be the case for the material used for this study which cracks preferentially at the ferriteaustenite interface, representing ~50% of the cracks in both samples (for SSRT-T1 only propagation type has be considered since most of the cracks are initially transgranular but they become intergranular or follow a δ-γ interface after some penetration). Based on results from Y. H. Lu et al [20], this can be related to the sample orientation (S-L) used for this work that imply ferrite austenite interfaces are perpendicular to stress direction, i.e., δ -γ interfaces are parallel to crack propagation. This stimulates higher strain localisation at the interface (therefore, more cracks) in addition to the differences accommodating stresses between ferrite and austenite.…”
Section: Local Strainmentioning
confidence: 99%
“…In an oxidizing environment, it will react with oxygen and form a passivation film on the surface to prevent further corrosion (Turnbull et al, 2003). However, in the petroleum industry, the fluid medium usually contains chloride ions, which can destroy the product scale film (Khan et al, 2002;Lu et al, 2014). Moreover, the medium is usually a twophase gas-liquid flow, which results in much more complicated flow characteristics than do single-phase flows.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 SCC has been the subject of study in recent years for different materials, because of the enormous damage it causes in structures. [13][14][15][16][17][18][19][20][21][22][23][24][25][26] The susceptibility of DSSs to SCC has recently been studied by Laitinen and Hanninen 27 who investigated SCC susceptibility in a 50 wt-% CaCl 2 solution at 100°C for the UNS S31803 DSS. They observed that crack propagation was mainly through the austenite phase.…”
Section: Introductionmentioning
confidence: 99%